Management Strategy and Outcome of Epidural Haematoma in Relation to Volume (Faridpur Medical College Journal, 2011)
Epidural Haematoma (EDH) develops in 1-3% of all major head injuries and most common in the young. This crosssectional descriptive study was done to find out the management strategy and outcome of EDH in relation to clot volume. This study was performed from December'2006 to November'2007, by purposively selecting 77 cases of EDH from the Department of Neurosurgery, Dhaka Medical College Hospital (DMCH), Dhaka. The study showed that highest number of patients was in most active period of life, with male predominance (Male: Female =7.5:1). Causes of EDH were mostly due to assault (37.7%), followed by RTA (32.5%) and fall from height (29.8%). The study showed Patient having EDH Volume (EDHV) > 30ml will have 8.55 times more chance of having unfavorable outcome than patient having EDHV < 30 ml. Patient having EDHV > 30 ml will have 187.83 times more chance of requiring surgical intervention than those having EDHV